2005
DOI: 10.1073/pnas.0504438102
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression evidence for remodeling of lateral hypothalamic circuitry in cocaine addiction

Abstract: By using high-density oligonucleotide arrays, we profiled gene expression in reward-related brain regions of rats that developed escalated cocaine intake after extended access to cocaine (6 h per day). Rats allowed restricted daily access to cocaine (only 1 h) that displayed a stable level of cocaine intake and cocaine naive rats were used for controls. Four analysis methods were compared: Affymetrix MICROARRAY SUITE 4 and MICROARRAY SUITE 5, which use perfect-match-minus-mismatch models, and DCHIP and RMA, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 75 publications
6
99
1
Order By: Relevance
“…Additional support for the idea that incubation of drug craving involves early withdrawal neuroadaptations that decrease cue-induced drug seeking comes from cocaine studies in which the duration of the training session and number of training days were manipulated (Pacchioni et al, 2011;Sorge et al, 2005). These studies indicate that extended cocaine exposure, which presumably leads to more profound neuroadaptations (Ahmed et al, 2005;Ben-Shahar et al, 2009), does not increase cue-induced drug seeking during late withdrawal but instead decreases cocaine seeking during early withdrawal. This idea is also supported by recent molecular studies that have documented differential transcriptional and translational adaptations at early and late withdrawal times after methamphetamine self-administration in rats (Krasnova et al, 2013).…”
Section: Incubation Of Methamphetamine and Food Craving In Unpunishedmentioning
confidence: 81%
“…Additional support for the idea that incubation of drug craving involves early withdrawal neuroadaptations that decrease cue-induced drug seeking comes from cocaine studies in which the duration of the training session and number of training days were manipulated (Pacchioni et al, 2011;Sorge et al, 2005). These studies indicate that extended cocaine exposure, which presumably leads to more profound neuroadaptations (Ahmed et al, 2005;Ben-Shahar et al, 2009), does not increase cue-induced drug seeking during late withdrawal but instead decreases cocaine seeking during early withdrawal. This idea is also supported by recent molecular studies that have documented differential transcriptional and translational adaptations at early and late withdrawal times after methamphetamine self-administration in rats (Krasnova et al, 2013).…”
Section: Incubation Of Methamphetamine and Food Craving In Unpunishedmentioning
confidence: 81%
“…As early as 1964, Wolf (38) showed that bilateral lesions in the lateral hypothalamus greatly reduced the drinking response to sodium deficiency, although he commented that such lesions might damage structures nearby (e.g., zona incerta and median forebrain bundle). Another study reported it as a brain subregion with particularly dynamic gene regulation in cocaineaddicted rats (39).…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably because extended access facilitates greater drug intake than limited access, and produces greater corresponding changes in the brain responsible for addiction-like behaviour (Mantsch et al 2004;Ahmed et al 2005;Ferrario et al 2005;.…”
Section: Do Procedures That Produce 'Addiction-like' Behaviour In Animentioning
confidence: 99%